Evaluasi pendidikan ekonomi informal dalam keluarga: Dampak sosial ekonomi terhadap metode dan nilai yang ditanamkan - Vindi Kusuma Wardani; Istiqomah Ahsanu Amala (Universitas Negeri Surabaya, 2025)
Informal economic education within families serves as a crucial foundation that shapes children's economic mindset from an early age. This study explores how parents' socioeconomic status influences teaching methods and the economic values instilled in their children. The research involves six families in Surabaya representing low, middle, and high socioeconomic classes. The evaluation employs the CIPP (Context, Input, Process, Product) model to analyze the relevance, resources, implementation, and outcomes of informal economic education. The findings reveal significant differences: families with higher socioeconomic status tend to use more complex methods, such as critical dialogue and strategic role modeling. Meanwhile, middle-class families rely on habit formation and dialogue to build financial management understanding. In contrast, families with lower socioeconomic status focus more on basic role modeling and simple habit-building. This study recommends that all parents enhance their awareness of the importance of economic education and apply methods tailored to their circumstances. Furthermore, there is a need for more inclusive and accessible formal economic education programs to support families across all socioeconomic levels in developing more effective teaching methods.